The Mythological and Philosophical Significance of Cattle in Nepal: An Exploration of Historical and Contemporary Perspectives (Sudurpaschim Spectrum, 2026)
In Eastern philosophy and spirituality, cattle have held a supreme position, which is not incidental but rather rooted in the profound medicinal properties attributed to them by ancient sages. However, in recent times, particularly in Nepal, it has been observed that people, driven by self-interest, exploit cattle for their milk and then abandon them once they become weak or unproductive. This issue has become particularly acute in Western Nepal, emerging as a significant social problem. On one hand, cattle are suffering, and on the other, individuals are losing their lives in road accidents caused by stray cattle. This research paper aims to present an in-depth study of the current status of cattle in Nepal and its impact on religious and agricultural heritage. It also seeks to raise awareness about the mythological and philosophical significance of cattle, discuss their agricultural importance, and highlight the scientific benefits derived from them. While much has been written about cattle and their importance, there is a noticeable lack of research based studies that encompass their mythological, philosophical, agricultural, and scientific significance. This paper fills that gap by providing a comprehensive exploration of these aspects. The study employs historical research methods, library research techniques, and comparative analysis. It identifies the issue of stray cattle as not only a symbol of the decline of indigenous development principles but also a reflection of the erosion of human values. While modern agricultural tools are necessary for development, this should not come at the expense of cultural preservation. Unfortunately, in Nepal, modernization has led to the destruction of cattle, which are traditionally considered protectors of health and wealth. This is a matter of grave concern. The paper is primarily based on secondary data from various books, journals, and other sources, and is qualitative in nature. Additionally, the views of individuals involved in cattle conservation and farmers practicing cattle rearing have been incorporated to provide primary insights. The paper underscores the necessity of preserving cattle, whose by-products, such as ghee, milk, urine, and dung, are vital for human life and the environment, and form the foundation of agriculture.